Pembelajaran Berdiferensiasi sebagai Inovasi pembelajaran - Kaniati Amalia; Istifadah Rasyad; Awan Gunawan (Journal of Education and Teaching Learning, 2023)
Differentiated learning is a process or philosophy for effective teaching by providing a variety of ways to understand new information for all students in their diverse classroom community, including ways to: acquire content; processing, building, or reasoning ideas; and developing learning products and assessment measures so that all students in a classroom of diverse abilities can learn effectively. This study aims to provide information about differentiated learning and its implementation in the midst of diversity with the heterogeneity of students' backgrounds which is a challenge in learning. Differentiated learning is a separate innovation in learning because differentiated learning is learning that accommodates all differences in students, is open to all and provides the needs needed by each individual. This research is a research that uses historical research/documentary study methods with data sources found using techniques to find information about the topic. The research results show that each student has different characteristics, not all students can be given the same treatment so that differentiation learning tends to be more suitable to be implemented.